OC-019 The evaluation of portal hypertension using quantitative magnetic resonance imaging (MRI). (22nd June 2015) - Palaniyappan, N; Cox, E; Guha, IN; Austin, A; O'Neill, R; Ramjas, G; Travis, S; White, H; Singh, R; Thurley, P; Francis, S; Aithal, GP
Abstract : Introduction: The majority of complications in liver cirrhosis results from portal hypertension. The hepatic venous pressure gradient (HVPG) is the gold standard measure to assess portal pressure but this requires hepatic vein catheterisation which is an invasive procedure and available in only a few specialised liver units. We aim to develop a novel non-contrast quantitative MRI methodology to estimate portal pressure. Method: We prospectively recruited patients undergoing HVPG measurement for clinical indications and MRI was performed within 6 weeks. A respiratory-triggered inversion recovery scheme was used to measure the longitudinal (T1 ) relaxation time of the liver and spleen employing a fat suppressed Echo Planar Imaging-acquisition. Phase-contrast (PC)-MRI was used to assess the velocity, area and bulk flow in the splanchnic circulation without any intravenous contrast agents. Results: 33 patients [alcoholic, 10 (30.3%); non-alcoholic fatty liver disease, 11 (33.3%); and autoimmune hepatitis, 5 (15.2%)], aged 55 ± 12 years (mean ± SD) were enrolled in this study. 4 patients were excluded due to claustrophobia (3) and non-cirrhotic portal hypertension (1). Liver and spleen T1 relaxation time correlated significantly with HVPG (R = 0.797, p < 0.001; R = 0.383, p = 0.037 respectively) (Figure 1 ). The correlation of HVPG with splanchnic and collateral haemodynamics is shown in Table 1 . Conclusion: We have demonstrated that parameters related to both hepatic architecture and splanchnic haemodynamics derived from non-contrast quantitative MR imaging techniques correlate significantly with HVPG. In future studies, these MRI techniques will be utilised for the non-invasive evaluation of portal hypertension. Disclosure of interest: None Declared.